Bombs, fire and biodiversity: Vertebrate fauna occurrence in areas subject to military training. (December 2016) - Lindenmayer, David B.; MacGregor, Christopher; Wood, Jeff; Westgate, Martin J.; Ikin, Karen; Foster, Claire; Ford, Fred; Zentelis, Rick
Abstract: Military training areas (MTAs) cover 6% of the earth's land surface, but the impact on biodiversity of weapons use in MTAs remains largely unknown. We quantified the effects of military training on vertebrates in a 5-year study at Beecroft Weapons Range in south-eastern Australia by contrasting the occurrence of birds, mammals and reptiles between 24 sites within an area subject to repeated weapons use and a matched set of non-impacted sites. Species richness of mammals and reptiles was similar within versus outside the impact area, although many individual species responded to fire, which occurred more frequently in impacted sites. Bird species richness, the occurrence of larger-bodied and migratory bird species, and the occurrence of most individual bird species, was reduced within the impact area. Many bird species that displayed low prevalence in impacted sites also declined over time across the whole study area. Differences in biota between the impact and non-impact areas were detectable after controlling for the effects of recent fire, suggesting that weapons use impacted vertebrates through mechanisms additional to altered fire regimes. Overall, our data indicated that Beecroft Weapons Range maintained considerable biodiversity value despite prolonged military use. Hence, MTAs have the potential to make a substantial contribution to conservation outside the formal protected area network. However, managers of MTAs need to explicitly state their environmental objectives. This is because management practices may be different if the aim is to maximize species richness rather than to secure populations of particular species. Highlights: Military training areas (MTAs) cover nearly 6% of the earth's land surface. Impacts on biodiversity of weapons use in MTAs is largely unknown. Our target MTA supported high biodiversity value despite prolonged military use. Mammal and reptile richness was similar within versus outside the impact area. Bird richness and occurrence of most bird species was reduced in the impact area.